Moral ambivalence and informal care for the dying - Broom, A; Kirby, E; Kenny, K; Macartney, J; Good, P (Wiley, 2016)
Caring for the dying presents perhaps the most challenging site of informal care. Participation in informal caring roles in such contexts has been prone to reification as a virtuous social practice, often without critical reflection as to the implications for caregivers. Here, drawing on interviews with carers who were providing care in the last few weeks or days of life, we develop an understanding of informal care in this setting as a morally ambiguous social practice, framed by social relations of duty, gift and virtue, but in turn encapsulating experiences of failure, shame and suffering. Such a contradictory understanding of caregiving is critical for understanding the tensions within end-of-life settings and also for countering the concealments produced by the valorization of informal care more broadly in modern societies. We present a critical analysis of informal care’s contested character at the end of life, challenging normative understandings that are complicit in producing moral ambivalence, shame and suffering for individual carers.